JOINT FARMING THROUGH NEIGHBOR HOOD GROUPS (NHG’S) IN KERALA : A CASE OF KUDUMBASHREE - Raj Kumar Pammi and M.M. Kadasiddappa (Progressive Research, 2014)
Kudumbashree launched in 1998 as a community network to work in tandem with local self governments for annihilation of poverty and women empowerment. Kudumbashree is one of the largest women’s movement in Asia with a membership of 41 lakh representating equal number of families. Collective farming is an initiative introduces by Kudumbashree to encourage cultivation by Neighborhood Groups (NHG’s). it facilitates to enhance agricultural production by bringing fallow and cultivable waste land into agricultural use, and has significance as a food security measure. Women enter the programme as cultivators as opposed to agricultural labour and control over the means of production and access to formal credit help in increasing the returns from farming. Joint Liability Groups ( JLG’s) of women farmers are formed under the collective farming initiative to help women cultivators access agricultural credit from the banking system. The paper highlights the various process of promoting the JLG’s of NHG’s women and how they take up collective farming in Idukki District of Kerala by presenting various case studies. Through the collective farming programme of NHG’s the twin benefits of poverty reduction, food security and financial returns through agriculture and increased agricultural production are being accomplished by the poor women.